Pengaruh Pemberian Pupuk Organik Cair Limbah Sayuran Terhadap Pertumbuhan dan Hasil Tanaman Kailan (Brassica oleraceae L.) Varietas Nita F1 - Nandang Saepuloh; Darso Sugiono; Hayatul Rahmi (UNIVERSITAS LABUHANBATU, 2026)
The use of liquid organic fertilizer contains various nutrients required for plant gowth, improves soil quality, enhances soil fertility, and reduces excessive use of inorganic fertilizers, thereby helping to enhance the gowth and yield of Kailan plants. This study aims to determine the optimal concentration of liquid organic fertilizer from vegetable waste that has the best effect on the gowth and yield of Kailan (Brassica oleracea L.) variety Nita F1. The experiment was conducted in Puseurjaya Village, Telukjambe Timur Subdistrict, Karawang Regency, West Java Province, Indonesia, from April to August 2024. The research method used was an experimental design with a single-factor randomized block design (RBD) consisting of 6 treatments in 5 replications: P0 (vegetable waste liquid organic fertilizer concentration 0 ml/l), P1 (vegetable waste liquid organic fertilizer concentration 100 ml/l), P2 (POC concentration of vegetable waste 200 ml/l), P3 (POC concentration of vegetable waste 300 ml/l), P4 (POC concentration of vegetable waste 400 ml/l), P5 (POC NASA 6 ml/l). The effects of the treatments were analyzed using an F-test at the 5% level, followed by a Duncan Multiple Range Test (DMRT) at the 5% level. The results showed that the treatments had a significant effect on plant gowth and yield. Treatment P4 (POC concentration of vegetable waste 400 ml/l) yielded the highest results for plant height (25.18 cm), stem diameter (5.61 mm), number of leaves (8.68 leaves), root length (14.68 cm), and fresh weight of the plant (33.84 g). Keywords: kailan, liquid organic fertilizer, vegetable waste